Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 196734 by sonukgindia last updated on 30/Aug/23

Answered by qaz last updated on 31/Aug/23

y′′y+(y′)^2 =(y′y)′=(1/2)((y^2 )′)′=3x  ⇒(y^2 )′=3x^2 +C_1     y^2 =x^3 +C_1 x+C_2   C_1 =−6       C_2 =3  ⇒y^2 =x^3 −6x+3

$${y}''{y}+\left({y}'\right)^{\mathrm{2}} =\left({y}'{y}\right)'=\frac{\mathrm{1}}{\mathrm{2}}\left(\left({y}^{\mathrm{2}} \right)'\right)'=\mathrm{3}{x} \\ $$$$\Rightarrow\left({y}^{\mathrm{2}} \right)'=\mathrm{3}{x}^{\mathrm{2}} +{C}_{\mathrm{1}} \:\:\:\:{y}^{\mathrm{2}} ={x}^{\mathrm{3}} +{C}_{\mathrm{1}} {x}+{C}_{\mathrm{2}} \\ $$$${C}_{\mathrm{1}} =−\mathrm{6}\:\:\:\:\:\:\:{C}_{\mathrm{2}} =\mathrm{3} \\ $$$$\Rightarrow{y}^{\mathrm{2}} ={x}^{\mathrm{3}} −\mathrm{6}{x}+\mathrm{3} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com